Stories We Live and Grow By: (Re)Telling Our Experiences as Muslim Mothers and Daughters - Shirin Khayambashi (Atlantis)
Book under review: Saleh, Muna. 2019. Stories We Live and Grow By: (Re)Telling Our experiences as Muslim Mothers and Daughters. Ontario, Canada: Demeter Press.